Pencatatan Utang pada Paguyuban Usaha Syar’i di Cikarang dalam Sudut Pandang Ekonomi Syariah - Nurul Iftiani; Adi Supriadi (Jurnal Al-fatih Global Mulia, 2023)
Muslims in muamalah maliyah should be guided by the provisions of the Shari'a and pay attention to how to find halal assets in a lawful way. Because every property obtained will be held accountable by Allah on the Day of Judgment about where the wealth was obtained and where it was donated. So it is very important for Muslims to understand and know transactions that are justified by the Shari'a in order to avoid illicit assets caused by elements of transactions that are prohibited by the Shari'a. As the background for the formation of the Syar'i Business Association (PUS) is to avoid dishonorable, ghoror and usury transactions. Among the things that need to be considered in muamalah are related to recording transactions in muamalah, one of which is muamalah which is done in cash or debt which is carried out in the Syar'i Business Association. Based on this background, this study aims to find out how debt is recorded at the Syar'i Business Association and what it looks like from a sharia economic perspective. As a basis for this study, the authors used the theory of sharia accounting principles in a book authored by Dr. Muammar Kaddafi., SE., M.Si et al entitled Sharia Accounting Putting Islamic Sharia Values in Accounting. The theory of recording based on Islamic accounting principles has 3 indicators, namely accountability, fairness and truth. To reveal the problem as a whole the author uses a library research method with a qualitative descriptive approach. The data analysis technique uses data reduction, namely the process of summarizing and choosing the main points, the researcher analyzes the data obtained both through interviews and documentation, then draws conclusions to find out the recording of debts at the Syar'i Business Association. From the results of this study it can be concluded that the recording of debt at the Syar'i Business Association is in accordance with sharia accounting principles. The principles of accountability, justice and truth are applied in the form of an application that contains information related to the debt records of association members that are easily accessible by each member.